2011
DOI: 10.1038/aja.2010.166
|View full text |Cite
|
Sign up to set email alerts
|

The number of spermatozoa collected with testicular sperm extraction is a novel predictor of intracytoplasmic sperm injection outcome in non-obstructive azoospermic patients

Abstract: The purpose of this study was to determine the relationships between monitors of spermatogenesis and predictors of the intracytoplasmic sperm injection (ICSI) outcome in patients with non-obstructive azoospermia (NOA) undergoing testicular sperm extraction (TESE). Seventy-nine patients with NOA (mean age: 43.6±5.2 years), each of whom yielded (97 000±3040) spermatozoa with conventional TESE, were considered in our analysis. Their partners (mean age: 35.8±5.1 years) underwent a total of 184 ICSI cycles; 632 ooc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The latter is strongly influenced by even a minimal improvement in spermatogenesis. 15 AUTHOR CONTRIBUTIONS GC wrote the paper and studied two cases. Giovanni Beretta and Giulio Biagiotti studied one case each.…”
Section: Resultsmentioning
confidence: 99%
“…The latter is strongly influenced by even a minimal improvement in spermatogenesis. 15 AUTHOR CONTRIBUTIONS GC wrote the paper and studied two cases. Giovanni Beretta and Giulio Biagiotti studied one case each.…”
Section: Resultsmentioning
confidence: 99%
“…Whitcomb et al (35) pointed out that male age, after being adjusted for female-partner age, was nonsignificantly associated with likelihood of live birth. Cavallini et al (36) reported a detrimental effect of the retrieved-sperm count on the outcome of ICSI. In this context, maternal age in our study was a nonsignificant variable, owing primarily to the fact that most female partners were aged <30 years.…”
Section: Discussionmentioning
confidence: 98%
“…The impact of an increased sperm count on the success of assisted reproduction techniques occurring after letrozole administration will be presented in a future study; however, because the quality of spermatogenesis in NOA patients is linked to intracytoplasmic sperm injection pregnancy rates, even mild improvement can improve the likelihood of pregnancy. 28 This might be particularly interesting for Italians since their law limits the efficiency of assisted reproduction treatment in couples with a severe male factor. 29,30 It is unlikely that letrozole increased congenital malformations, as no malformed babies were fathered during the course of letrozole treatment.…”
Section: Letrozole For Azoospermia and Cryptozoospermia G Cavallini Ementioning
confidence: 99%